2021
DOI: 10.3390/antibiotics10080952
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic and Acyclic Amine Oxide Alkyl Derivatives as Potential Adjuvants in Antimicrobial Chemotherapy against Methicillin-Resistant Staphylococcus aureus with an MDR Profile

Abstract: The dramatic intensification of antimicrobial resistance occurrence in pathogenic bacteria concerns the global community. The revitalisation of inactive antibiotics is, at present, the only way to go through this health system crisis and the use of antimicrobial adjuvants is turning out the most promising approach. Due to their low toxicity, eco-friendly characteristics and antimicrobial activity, amphoteric surfactants are good candidates. This study investigated the adjuvant potentialities of commercial acyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 68 publications
(83 reference statements)
1
13
0
Order By: Relevance
“…Antibiotic adjuvants include: (1) anti-resistance drugs such as β-lactamase inhibitors pump inhibitors, membrane permeabilizers, and biofilm inhibitors; (2) antivirulence drugs, such as quorum-sensing inhibitors, toxin inhibitors, and secretion system inhibitors; (3) host-directed therapies such as innate immune system agonists and immunomodulatory peptides; and (4) other therapies such as phage, probiotic, and oral rehydration therapies ( Gill et al, 2015 ). Various synthetic and natural compounds such as prazolopyridazine derivatives ( Schaenzer et al, 2018 ), isoflavonoids ( Abreu et al, 2017 ), plant extracts ( Abreu et al, 2016 ), cationic peptides ( Geitani et al, 2019 ), cannabidiol ( Wassmann et al, 2022 ), marine bisindole alkaloid ( Campana et al, 2020 ), cinnamonitrile ( Speri et al, 2019 ), amine oxide alkyl derivatives ( Fagnani et al, 2021 ), and brominated carbazoles ( Berndsen et al, 2022 ) have been recently proposed to be used as antibiotic adjuvants against S. aureus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic adjuvants include: (1) anti-resistance drugs such as β-lactamase inhibitors pump inhibitors, membrane permeabilizers, and biofilm inhibitors; (2) antivirulence drugs, such as quorum-sensing inhibitors, toxin inhibitors, and secretion system inhibitors; (3) host-directed therapies such as innate immune system agonists and immunomodulatory peptides; and (4) other therapies such as phage, probiotic, and oral rehydration therapies ( Gill et al, 2015 ). Various synthetic and natural compounds such as prazolopyridazine derivatives ( Schaenzer et al, 2018 ), isoflavonoids ( Abreu et al, 2017 ), plant extracts ( Abreu et al, 2016 ), cationic peptides ( Geitani et al, 2019 ), cannabidiol ( Wassmann et al, 2022 ), marine bisindole alkaloid ( Campana et al, 2020 ), cinnamonitrile ( Speri et al, 2019 ), amine oxide alkyl derivatives ( Fagnani et al, 2021 ), and brominated carbazoles ( Berndsen et al, 2022 ) have been recently proposed to be used as antibiotic adjuvants against S. aureus strains.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that the ability to inhibit microbial growth varies with the number of methylenes present in the l -prolinol derivative skeleton, in agreement with literature reports. 25 , 31 , 47 , 48 In general, the higher the lipophilicity of the surfactant, the stronger the interactions with cell structures. 31 , 49 These considerations can be simplistic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, surfactants bearing the N -oxide moiety can prevent protein–protein interaction 23 and confer antibacterial or antioxidant properties to the aggregates, depending on their molecular scaffold. 24 , 25 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can only be speculated whether the different courses of dependences of bactericidal activities against S. aureus ATCC 29213/MRSA SA 3202 (MRSA3) from isolates MRSA1/MRSA2 could be due to their differences in the composition of bacterial membranes [55][56][57][58]. The effect of changing the length of the hydrocarbon tail affecting the extent of antimicrobial activity of the compounds has been discussed (e.g., [36,37,[39][40][41][42][43][44]59,60]). The decrease in biological activity at a higher chain length as a cut-off effect is discussed above.…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%